Long-Range GABAergic Projections of Cortical Origin in Brain Function - Urrutia-Piñones, Jocelyn; Morales-Moraga, Camila; Sanguinetti-González, Nicole; Escobar, Angelica P.; Chiu, Chiayu Q. (Frontiers in Systems Neuroscience, 2022)
The study of long-range GABAergic projections has traditionally been focused on those with subcortical origin. In the last few years, cortical GABAergic neurons have been shown to not only mediate local inhibition, but also extend long-range axons to remote cortical and subcortical areas. In this review, we delineate the different types of long-range GABAergic neurons (LRGNs) that have been reported to arise from the hippocampus and neocortex, paying attention to the anatomical and functional circuits they form to understand their role in behavior. Although cortical LRGNs are similar to their interneuron and subcortical counterparts, they comprise distinct populations that show specific patterns of cortico-cortical and corticofugal connectivity. Regardless, cortical LRGNs mainly innervate inhibitory interneurons to likely induce disinhibition in target regions. Thus, LRGNs are emerging as a new element of cortical output, acting in concert with long-range excitatory projections to shape brain function in health and disease.